2015
DOI: 10.2322/tjsass.58.213
|View full text |Cite
|
Sign up to set email alerts
|

Sputtering Yield of Carbon-Carbon Composite Due to Xenon Ion Bombardment in Ion Engines

Abstract: The angular and energy dependence of the sputtering yield of a carbon-carbon composite due to xenon ion bombardment was investigated. Instead of assuming surfaces to be flat, a simple carbon fiber distribution model was introduced to account for the carbon-carbon composite surface structure observed using a scanning electron microscope. Yamamura's semi-empirical sputtering formula, which accounted for 14% xenon adsorption, was used to calculate the sputtering yield of the carbon fiber surface. The proposed mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…52 Larger scale cylindrical structures formed by individual graphite fibers in carbon-carbon composites produce similar effects. 53 The results reviewed here provide conflicting evidence about the effect of μm-scale roughness on yield. Williams found that the yield on pyrolytic graphite for 1 keV xenon ions with a global incidence angle of 30 increased about 17% over the initial yield and stabilized after 2-2.5 μm were removed.…”
Section: Surface Roughness Effectsmentioning
confidence: 90%
“…52 Larger scale cylindrical structures formed by individual graphite fibers in carbon-carbon composites produce similar effects. 53 The results reviewed here provide conflicting evidence about the effect of μm-scale roughness on yield. Williams found that the yield on pyrolytic graphite for 1 keV xenon ions with a global incidence angle of 30 increased about 17% over the initial yield and stabilized after 2-2.5 μm were removed.…”
Section: Surface Roughness Effectsmentioning
confidence: 90%
“…The sputtering yield of the grid material was incorporated using the sputtering model in the form of tables of values for incident energies and incident angles. 15) The computational region of the analysis is a prism-shaped 30°-60°-90° region. We employed fine meshes (less than the Debye length) for the discharge and neutralization plasma regions.…”
Section: Computational Methods and Conditionsmentioning
confidence: 99%
“…Once this highest temperature estimation method is established, it will be useful not only for the aforementioned applications but also for supersonic aircraft parts and various engines. [22][23][24] Raman analysis is a commonly used technique for the evaluation of the degree of graphitization. Tallant et al 25) presented the temperature dependent Raman spectra for a heated rayon CFRP, which is a rayon-based carbon fiber-reinforced phenolic resin composite.…”
Section: Introductionmentioning
confidence: 99%